Influence of Lean Supply Chain on Performance of Public Universities in Kenya - Mwangangi, Jackline; Achuora, John (IJSSIT, 2019)
Purpose:The main objective of this study was to determineinfluence of lean supply chain on performance of Public Universities in Kenya.Materials and methods;this research adopted descriptive design. A descriptive research is a method of collecting information by interviewing or administering questionnaire to a sample of individuals. Descriptive design as the most appropriate design in getting responses from respondents who participate by answering questions. The target population of this study was from employees in administration, accounts and procurement departments in public universities. The unit of observation for the study was the. Public Universities in Kenya and the unit of analyses for the study was the employees working in administration, accounts and procurement departments. This study sampled all public universities in Kenya, the researcher used census since data collection through census method gives opportunity to the researcher to have an intensive study about a problem study about a problem, census also ensure a higher degree of accuracy in data no other method is accurate like census method. The study used the most common internal consistency measure known, as Cronbach’s alpha (α) in testing the reliability of the instrument. The alpha indicates the extent to which a set of test items can be treated as measuring a single latent variable. The data collected from the field was analyzed qualitatively and quantitatively.At first, data was screened to identify omissions and removal of non –answered questions. For quantitative data analysis, coding and entry was done in electronic spread sheet with the aid of Statistical Package for Social Sciences (IBM SPSS Version 23). Data generated from SPSS was analyzed using descriptive and inferential statistics whereby the output was presented using tables, pie charts and graphs.Results: The study established a significant positive relationship between Lean Supply chain and Organizational Performance. This implies that an increase in on organizational performance in public universities in Kenya is likely through adoption of Lean Supply chain initiatives.Recommendations:The study recommendation that Lean supply chain management requires public universities to examine every process in their supply chain since This will improve the organisation competitiveness as well as improve the organisation overall profitability.Keywords:Lean Supply chain, Supply base rationalization, Framework contracting, Supply chain visibility, Continuous Improvement
Keywords: Lean Supply chain; Supply base rationalization; Framework contracting; Supply chain visibility; Continuous Improvement